Impact of Celebrity Endorsement and Breaking News Effect on the Attention of Consumers - Lazar, Laura; Pop , Mihai-Ionuţ (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2021)
In the last decade, the new means of communication have determined substantial changes in human behavior and in the way individuals interact with each other. Besides the numerous benefits and opportunities that have arisen throughout the digitalization process, both for individuals as well as for private companies and state institutions, the widespread use of the Internet has generated vulnerabilities and threats. One of the most consistent concerns related to the new means of communication, especially social media platforms, refers to fake news. In recent years, major events including the 2016 presidential election in the US, Brexit, and the emergence of the COVID-19 pandemic have proven the negative effects of fake news on society. In this paper, we use an eye-tracking experiment to determine the unconscious reactions of consumers regarding the attraction potential of a fake news manner written article about a celebrity couple. The results of the experiment for this magazine`s article, with a fake title about the celebrity couple, show that the participants focus their attention on celebrities and fake titles mostly. The picture of the celebrities and the fake title of the article beats the other areas from the article and less on the information in the text. The research proves empirically that consumers are more attentive to celebrity pictures and fake breaking news titles and less to real information in the article. To sum up, testimonials and fake news play an important role in attracting publicity and influencing consumer behavior.